2020
DOI: 10.5713/ajas.19.0545
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with different types of fiber in gestation and lactation: effects on sow serum biochemical values and performance

Abstract: Objective: Three types of dietary fiber were fed to sows during gestation and lactation stages to monitor their physiological and metabolic adaptations during the pre-partum period and to determine how these effects may influence the lactation period and sow performance.Methods: Soon after breeding, 54 sows were selected and were fed with 20% supplementation as fed of wheat bran (WB), soya hulls (SH), or rice hulls (RH) in diets during gestation and lactation. Sows were weighed, backfat thickness was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Interestingly, a lower stillbirth rate (SR) was reported when sows were fed mixed DF sources during gestation (Feyera et al, 2017;Huang et al, 2020). An increased litter birth and weaning weight (Veum et al, 2009;Weng, 2020) as well as improved colostrum intake and preweaning survival of the pigs (Guillemet et al, 2007;Loisel et al, 2013;Theil et al, 2014) were observed in sows fed high DF diets. On the other hand, supplementation of extra energy during the transition period is important to improve energy status of the sow at farrowing and the farrowing process (Feyera et al, 2018;Nielsen et al, 2021).…”
Section: Introductionmentioning
confidence: 95%
“…Interestingly, a lower stillbirth rate (SR) was reported when sows were fed mixed DF sources during gestation (Feyera et al, 2017;Huang et al, 2020). An increased litter birth and weaning weight (Veum et al, 2009;Weng, 2020) as well as improved colostrum intake and preweaning survival of the pigs (Guillemet et al, 2007;Loisel et al, 2013;Theil et al, 2014) were observed in sows fed high DF diets. On the other hand, supplementation of extra energy during the transition period is important to improve energy status of the sow at farrowing and the farrowing process (Feyera et al, 2018;Nielsen et al, 2021).…”
Section: Introductionmentioning
confidence: 95%
“…Fibers refer to plant cell wall components, such as cellulose and hemicellulose, which need to be fermented in the gastrointestinal tract to provide energy. A fiber-rich diet during gestation increases female reproductive success through modulation of her gut microbiota composition, with consequences for the offspring's immune development (T cell maturation, antioxidant defense) and birth weight (mice (Mus musculus): Nakajima et al 2017;humans: Hu et al 2019;domestic pigs: Li et al 2019;Weng 2019;Zhuo et al 2020). Consuming more fibers during gestation may be selected in Assamese macaques for its beneficial effect on female reproductive performance.…”
Section: Gestationmentioning
confidence: 99%
“…In the above studies, beet pulp and flaxseed meal mainly included soluble fiber, while bran, oat hulls, and feeding bamboo powder mainly included insoluble fiber, indicating that serum total cholesterol and triglyceride levels might be associated with dietary fiber level instead of fiber sources. Another study showed that the effects of fiber type on serum biochemical parameters for lipid metabolism were different at different stages of sows ( Weng, 2020 ). Thus, it was necessary to explore the regulation effect of feeding bamboo powder in different physiological stages, and its effects on fat digestibility and milk fat content in sows.…”
Section: Discussionmentioning
confidence: 99%